Extremely Low Frequency Electric and Magnetic Field Investigation of 132 KV Transmission Lines and Substations in Oman - Shaik Abdul Saleem (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This study focuses on examining the longitudinal and lateral impacts of electric and magnetic fields generated by 132 kV transmission lines in the Sultanate of Oman. The longitudinal and lateral measurements of the electric and magnetic field profiles of 132 kV power lines are being conducted at three specific places within the Sultanate of Oman, namely Al Buraimi, Khaboora, and Rustaq. The analysis of electric and magnetic fields emitted by transmission lines involves the utilisation of an EHP-50F E&H field analyzer sensor unit and an environmental metre. The on-site measurements of the 132kV transmission line are being compared to the International Commission for the Protection against Non-ionizing Radiation (ICNIRP) standard for electromagnetic field exposure in both public areas and workplaces. The measurements were conducted at 132kV transmission lines or to a distance of the insignificant field at the high-voltage substation. The components included power transformers, current transformers (CT), potential transformers (PT), circuit breakers, reactors, earth switches, transport couplers, lightning arrestors, and others. This study conducted in Oman represents the primary investigation of multiple elements related to the Oman Electricity Transmission Company (OETC) and its technical standards, which are based on optimal practices. The Sultanate of Oman has established an objective for the year 2030 to construct a state-of-the-art smart transmission grid with the purpose of efficiently transmitting and distributing power in a manner that is both secure and cost-effective. This article presents a systematic approach to the implementation of a smart transmission grid.